2016
DOI: 10.1039/c6an00440g
|View full text |Cite
|
Sign up to set email alerts
|

Can solvent induced surface modifications applied to screen-printed platforms enhance their electroanalytical performance?

Abstract: In this paper the effect of solvent induced chemical surface enhancements upon graphitic screen-printed electrodes (SPEs) is explored. Previous literature has indicated that treating the working electrode of a SPE with the solvent N,N-dimethylformamide (DMF) offers improvements within the electroanalytical response, resulting in a 57-fold increment in the electrode surface area compared to their unmodified counterparts. The protocol involves two steps: (i) the SPE is placed into DMF for a selected time, and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
(53 reference statements)
1
25
0
Order By: Relevance
“…Indeed, E p for the Ru(NH 3 ) 6 3+/2+ redox couple with SPCEs prepared from custom-formulated inks was found to depend on the ratio of poly(vinyl chloride) binder to conductive pyrolytic graphite particles, with inks that featured lower percentages of binder producing smaller E p . 30 Surface treatments, such as exposure to organic solvents 26,45 and mechanical polishing, 18,31 have also been found to affect E p for common redox couples. Peak currents for Fe(CN) 6 3−/4− increased by ∼8x for SPCEs after mechanical polishing using an agate lapping hammer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, E p for the Ru(NH 3 ) 6 3+/2+ redox couple with SPCEs prepared from custom-formulated inks was found to depend on the ratio of poly(vinyl chloride) binder to conductive pyrolytic graphite particles, with inks that featured lower percentages of binder producing smaller E p . 30 Surface treatments, such as exposure to organic solvents 26,45 and mechanical polishing, 18,31 have also been found to affect E p for common redox couples. Peak currents for Fe(CN) 6 3−/4− increased by ∼8x for SPCEs after mechanical polishing using an agate lapping hammer.…”
Section: Discussionmentioning
confidence: 99%
“…From the comparison, it can be seen that the proposed electrode shows broad linear range and a detection limit slightly above the other disposable electrodes. Although, we found that our paper electrodes are better in terms of electrode cost, they are flexible and they do not need to be electrochemical, physical or chemical activated before the analysis as it was shown that happen with screen printed electrodes . Pyrolyzed paper electrodes present several advantages as low cost, easy fabrication, LOD and linear range for Pb detection , which can be a promising option for laboratory applications.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation in this area usually explores the mediator use or the surface modification to improve the electrochemical detection [15,21,[24][25][26][27][28]. Some literature has been published related to the study of the redox couple NADH/NAD + in screen printing electrodes [1,4,21,[24][25][26][27][29][30][31][32][33][34]. The sensor built using this technique can incorporate the three electrodes (working electrode, reference and counter electrode), can be easily produced and miniaturized, work with a minimum volume (2 µL), it needs low reagent consumption, it can be fabricated in many supports (paper, glass) and sensors are disposable devices that can be used in many science fields [26,35].…”
Section: David Publishingmentioning
confidence: 99%